2018
DOI: 10.1111/dme.13794
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring women's health behaviours after a pregnancy with gestational diabetes to inform the development of a diabetes prevention strategy

Abstract: This study identified some common drivers that may regulate the health behaviours of women following GDM, and recognized some ways to improve care to impact on this. Interventions for diabetes prevention in this population need to address factors at both the individual and systemic levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 28 publications
8
58
0
Order By: Relevance
“…The first is that GDM is not a serious diagnosis that warrants undue concern. Although there is often an initial strong emotional response to a diagnosis of GDM that has been noted in other studies, this response tends to ease for many women over time, evolving into a view of GDM as a manageable condition [8,9,24]. Postdelivery, as in the present study, this view is then reinforced when women deliver 'happy, healthy' babies with 'no complications'.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The first is that GDM is not a serious diagnosis that warrants undue concern. Although there is often an initial strong emotional response to a diagnosis of GDM that has been noted in other studies, this response tends to ease for many women over time, evolving into a view of GDM as a manageable condition [8,9,24]. Postdelivery, as in the present study, this view is then reinforced when women deliver 'happy, healthy' babies with 'no complications'.…”
Section: Discussionsupporting
confidence: 58%
“…In general, despite using a novel methodological approach, our results were not inconsistent with results from other more traditional studies in this area. There was one notable difference in that postpartum abandonment has been an issue that is frequently identified as: eliciting frustration and concern for mothers post-delivery [27]; conveying a sense that the consequences of GDM are not serious enough to warrant follow-up post-delivery [8]; or diminishing the importance of women's own health by seeing them as baby machines [9]. Although some of our users had yet to deliver, it is notable that such abandonment was barely mentioned by any.…”
Section: Discussionmentioning
confidence: 99%
“…European studies of women who were overweight in pregnancy showed that 91% thought partner support and other social support were important in improving their lifestyle in pregnancy [15]. In qualitative studies of women with PE or GDM, the women state that their partner is important in supporting their lifestyle modification following gestational disease [16,17,33]. Nevertheless, our informants reported that the women had not directly asked their partners for support to change their lifestyle.…”
Section: Discussionmentioning
confidence: 90%
“…Consequently, health education and training are important for continuous blood glucose management [10]. However, pregnant women who are found to have GDM may not know much about the disease or blood glucose management because they have not experienced the disease before [10], and most pregnant women experience anxiety, depression, fear, and stress about responding to health problems that may negatively affect the fetus [11]. The adaptations required to manage GDM, in addition to the physiological and psychological changes of pregnancy, cause additional stress regarding blood glucose control and disease burden, which can reduce the effectiveness of treatment [12].…”
Section: Introductionmentioning
confidence: 99%